The world in a wineglass : the insider's guide to artisanal, sustainable, extraordinary wines to drink now - Isle, Ray (Scribner, 2023)
"Drawing on his deep knowledge and genuine appreciation of winemaking, Isle takes us on a tour of several hundred independently owned wineries around the world-everywhere from France's Burgundy to Oregon's Willamette Valley to the Itata Valley in the southern reaches of Chile-bringing the local vintners to life and describing the different wines they produce in vivid detail. Isle's enthusiasm for the grape growers and winemakers who are working sustainably or organically shines through as he shares his love for the way a glass of wine can express the place it comes from and capture the essence of the person who made it. Focusing on wines people can afford, rather than $500 rarities, Isle shows us where and how to find the most interesting bottles out there today"--